Spatial patterns of tree recruitment in East African tropical forests that have lost their vertebrate seed dispersers - Babweteera, F; Brown, N (Cambridge University Press, 2010)
The direct removal of adult trees by logging affects tree recruitment in tropical rain forests. However, secondary effects of logging, such as loss of vertebrate seed dispersers may also affect tree recruitment. We studied the recruitment and spatial distribution of five tree species namely Balanites wilsoniana, Celtis zenkeri, Chrysophyllum albidum, Cordia millenii and Ricinodendron heudelotii in Kibale, Budongo and Mabira Forests in Uganda. These forests have been subjected to varying degrees of disturbance leading to changes in their vertebrate seed dispersers. Vertebrate frugivores of the five tree species were identified. Three 1-ha plots were established around adult trees of the same five species in each forest and the distance from the juveniles to the nearest adult conspecific was measured to generate a recruitment curve. Frugivore visitation rates were high in the less disturbed Budongo and Kibale (2.2 and 1.6 individuals h⁻¹ respectively) compared with the highly disturbed Mabira (0.9 individuals h⁻¹). In the frugivore-impoverished forest, 70-90% of juveniles established beneath adult conspecifics, whereas in the less-disturbed forests juveniles were established up to 80 m from adult conspecifics. Shade-tolerant species capable of recruiting beneath adult conspecifics appeared to maintain their populations without dispersal. Consequently, disturbances leading to significant loss of vertebrates may alter tree recruitment and spatial distribution with consequences for long-term population viability of shade-intolerant tropical trees.